Política de formação profissional : o Programa Nacional de Acesso ao Ensino Técnico e Emprego (PRONATEC) em Mato Grosso - Silva, Gleyson Cezar Leme da (2018)
Throughout the last 15 years, the Professional and Technological Education (EFA) has undergone major transformations, mainly due to the increase in investments by the Federal Government in this area, resulting in the creation of new public policies focused especially on vocational training of young Brazilian students. In this context, no measure had greater impact than the creation in 2011 of the National Program for Access to Technical Education and Employment (Pronatec), whose main objectives are to expand, internalize and democratize the provision of courses of this type of education throughout the Brazil. This research aims at discussing the relationship between Work and Education present in this Public Policy of Vocational Training, clarifying the main intentions underlying this Program, as well as describing how this vocational training policy was initiated and implemented in the state of Mato Grosso. It is a qualitative research, based on the theoretical and methodological assumptions of the authors aligned with the current of Marxist thought, and the methodological procedure for its accomplishment was based on the literature review, a documentary analysis in the dialectical-materialist perspective, besides of the application of a questionnaire to three suppliers of the Program in the state of Mato Grosso. This discussion made it possible to observe the contradictions that occurred in the Program, in addition to questioning the real intentions of the program, since, despite having a large number of providers in the public and private networks, it presented a propensity for its execution to be carried out, preferably by the private initiative, constituting, eminently, a policy to meet the interests of capital.